Single incision prone retroperitoneoscopic paediatric nephrectomy. Issue 5 (October 2015) - Featherstone, Neil C.; De Win, Gunter; Undre, Shabnam; Cherian, Abraham
Summary: Objective: We have previously reported our early experience (2 patients) of single-incision nephrectomy via the retroperitoneal prone route using an advanced access platform (GelPOINT Mini). Here, we review our series to date and also present a detailed video demonstrating the technique. Method: In the prone position, a single transverse incision was made at the midpoint on a line along the lateral border of erector spinae bounded by the lower border of the 12th rib and iliac crest. Posterior abdominal muscles were split and the deep lumbodorsal fascia incised. The Alexis retractor was positioned and the Gel-Seal cap with low-profile sleeves locked in place. Hilar vessels were divided by endoclip application or harmonic scalpel. The kidney was retrieved directly or via an endobag. The Alexis retractor was removed and wound closed with absorbable sutures. Results: Between July 2013 and March 2015, we have used this approach to perform 10 nephrectomies in nine patients (4 male and 5 female). The median age at nephrectomy was 10.9 years (range 2.7–15.9 years). The median kidney length was 7.5 cm (range 3.7–11.5 cm). No complications occurred and none converted to open procedure. Conclusion: Single incision retroperitoneal nephrectomy is feasible, safe, and provides excellent cosmesis.